Fiber Optic Broadband Ultrasonic Probe for Virtual Biopsy: Technological Solutions. (31st October 2010) - Biagi, E.; Cerbai, S.; Masotti, L.; Belsito, L.; Roncaglia, A.; Masetti, G.; Speciale, N.
Abstract : An ultrasonic probe was developed by using, in conjunction, optoacoustic and acousto-optic devices based on fiber optic technology. The intrinsic high frequency and wide bandwidth associated both to the opto-acoustic source and to the acousto-optic receiving element could open a way towards a "virtual biopsy" of biological tissue. A Micro-Opto-Mechanical-System (MOMS) approach is proposed to realize the broadband ultrasonic probe on micromachined silicon frames suited to be mounted on the tip of optical fibers.